ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP KINERJA PERUSAHAAN GO PUBLIC SUB SEKTOR PROPERTY DAN REAL ESTATE - Nisa Medithiana; Ela Widasari; Siti Mudawanah (The Asia Pacific Journal Of Management Studies, 2024)
Company performance is a series of processes that are referred to and measured over a certain period of time based on an agreement that has been made previously. This study aims to examine and analyze the implementation of Good Corporate Governance (GCG) on the performance of service industry companies in the property and real estate sub-sectors listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The method used in this research is the quantitative method. The sample of this research is 12 property and real estate sub-sector service industry companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. Company performance is measured using Tobin's Q value, and using purposive sampling technique. The analysis technique used is multiple linear regression analysis technique using the SPSS V.20 . program The results of the study show that for the t-test there is a partial effect between the size of the board of directors, independent board of commissioners and audit committee on company performance. As for the F test, there is a significant effect between the size of the board of directors, the independent board of commissioners, and the audit committee on the company's performance simultaneously.